2021
DOI: 10.5751/es-12280-260220
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of urban resilience based on the transformation of resource-based cities: a case study of Panzhihua, China

Abstract: Long-term development of resource utilization has caused a series of economic, social, and ecological problems in resource-based cities (RBCs). Thus, in pursuit of sustainable urban development, many RBCs have begun seriously pursuing urban transformation and have achieved good results. However, the RBCs' urban resilience also exhibits evident stage characteristics throughout the processes of urban transformation. Herein, we constructed an evaluation index system to measure the urban resilience of Panzhihua, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Nonetheless, our study found that the industrial structure between cities along the YREB's lower reaches is required to be optimized, and TI's development needs to continue to increase (Cui et al, 2021). Secondly, education investment symbols the development potential of the city from the perspective of social development (Yang et al, 2021a), and wage income indicates the development status of the city. The more unbalanced the investment in education and residents' income, the ability to resist external shocks will be weaker (Hahn et al, 2017;Lewin et al, 2018).…”
Section: Fig 8 Spatial Differentiation Of Ur Along the Yreb's Lower Reachesmentioning
confidence: 83%
“…Nonetheless, our study found that the industrial structure between cities along the YREB's lower reaches is required to be optimized, and TI's development needs to continue to increase (Cui et al, 2021). Secondly, education investment symbols the development potential of the city from the perspective of social development (Yang et al, 2021a), and wage income indicates the development status of the city. The more unbalanced the investment in education and residents' income, the ability to resist external shocks will be weaker (Hahn et al, 2017;Lewin et al, 2018).…”
Section: Fig 8 Spatial Differentiation Of Ur Along the Yreb's Lower Reachesmentioning
confidence: 83%
“…income, fisherman's catch; Björkvik et al, 2020; Hänke et al, 2017). We used a composite system state index to aggregate state variables and trace the development trajectories of a social–ecological system; the lower the index, the more undesirable the system state, and vice versa (Yang et al, 2021). Using the abrupt point detection method (Verbesselt, Hyndman, Newnham, et al, 2010; Verbesselt, Hyndman, Zeileis, et al, 2010), the development trajectory of a system can be divided into different change periods.…”
Section: Methodsmentioning
confidence: 99%
“…Six core system state indicators were used to obtain the composite system state index that includes: the net income per capita of rural households, the ecosystem goods supply indices (grain, fruits, oil crops and cotton) and the sediment load of the Yellow River. These indicators were first normalized using the MAX‐MIN method (Equations 2 and 3), which allows for comparability (Yang et al, 2021). We set the maximum normalized value at 0.996 and the minimum normalized value at 0.002.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Xun et al[53]; Chen et al[72];Yang et al[73]; Assarkhaniki et al[74];Zhu et al[75], etc.Social resilience Social capital; Population density; Educational status; Number of doctors in the public health system; Health technicians per 10,000 people; Pupil-to-teacher ratio at public schools; Per capita post and telecommunications business volume; Number of doctors per 10,000 population, etc. Zhou et al [43]; Xun et al [53]; Chen et al [72]; Assarkhaniki et al [74]; Zhu et al [75]; Qasim et al [76]; Chen et al [54], etc.…”
mentioning
confidence: 99%